2021
DOI: 10.3390/cells10061344
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Trafficking via Lymphatic Vessels in Atherosclerosis

Abstract: In recent years, lymphatic vessels have received increasing attention and our understanding of their development and functional roles in health and diseases has greatly improved. It has become clear that lymphatic vessels are critically involved in acute and chronic inflammation and its resolution by supporting the transport of immune cells, fluid, and macromolecules. As we will discuss in this review, the involvement of lymphatic vessels has been uncovered in atherosclerosis, a chronic inflammatory disease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 128 publications
1
8
0
Order By: Relevance
“…We identified distinct fibroblast subsets as the main cellular source of VEGF-C production. It has been shown that lymphatic vessels mainly exist within the adventitial vessel wall, especially when atherosclerotic plaques possess a high expression level of VEGF-C. 36 We observed an intrinsic colocalization of fibrosis and lymphatic vessels within vascular allografts, supporting the notion that local fibroblasts release VEGF-C to directly stimulate lymphangiogenesis in situ.…”
Section: Discussionsupporting
confidence: 82%
“…We identified distinct fibroblast subsets as the main cellular source of VEGF-C production. It has been shown that lymphatic vessels mainly exist within the adventitial vessel wall, especially when atherosclerotic plaques possess a high expression level of VEGF-C. 36 We observed an intrinsic colocalization of fibrosis and lymphatic vessels within vascular allografts, supporting the notion that local fibroblasts release VEGF-C to directly stimulate lymphangiogenesis in situ.…”
Section: Discussionsupporting
confidence: 82%
“…VV is a specialized microvasculature that transports nutrients and oxygen to the adventitia and two-thirds of the media layer within the aortic wall. Adventitial lymphatic vessels modulate inflammation of the aortic wall by draining interstitial fluid and trafficking the immune cells through the aortic wall ( Kutkut et al, 2015 ; Yeo et al, 2021 ). Perivascular innervation in the adventitia modulates functions of VSMCs and ECs to regulate vascular tone ( Nava and Llorens, 2019 ).…”
Section: Anatomy Of Aortamentioning
confidence: 99%
“…Leukocyte egression from the plaques plays a critical role in atherosclerosis. 46,47 Thus, we quantified the ability of neutrophils, isolated from either healthy controls or patients, to migrate across a monolayer of LECs in the presence or absence of a chemoattractant (IL-8: 5 ng/ml) (schematic illustration, Figure 5A). There was no difference in spontaneous transmigration of neutrophils from controls or patients (Figure 5B).…”
Section: Lipoxin B 4 Treatment Enhances Lymphatic Transmigration Of N...mentioning
confidence: 99%